THE EVOLVING RELATIONSHIP BETWEEN ISLAMIC ECONOMIC THEORY AND FIQH AL-MUAMALAT IN MODERN FINANCIAL SYSTEMS: A COMPREHENSIVE ANALYSIS - Mansyur, Abdussalam; Asnawi, Nur; Khasanah, Umrotul; Jakfar Shodiq (University of Islam Malang, 2025)
This research examines the dynamic relationship between Islamic economic theory and fiqh al-mu'amalat in the context of modern financial systems. Using a systematic literature review method, this study analyzes the development of both disciplines and their interaction in shaping contemporary Islamic financial practices. The results indicate a significant convergence between Islamic economic principles and the interpretation of fiqh al-mu'amalat, especially in responding to modern financial challenges. However, several areas of tension requiring further harmonization were also identified. This study contributes to a more comprehensive understanding of how Islamic theory and legal practice interact in shaping the global Islamic financial landscape, while highlighting opportunities and challenges in developing innovative yet Shariah-compliant Islamic financial products.